Strategies for social and environmental disclosure: the case of multinational gambling companies - Leung, Tiffany Cheng-Han (Journal of business ethics, 2021)
This study investigates how firms in the gambling industry manage their corporate social disclosures (CSDs) about controversial issues. We performed thematic content analysis of CSDs about responsible gambling, money laundering prevention and environmental protection in the annual reports and stand-alone CSR reports (2009-2016) of four USA-based multinational gambling firms and their four Macao counterparts. This study draws on impression management theory, camouflage theory and corporate integrity theory to examine the gambling firms’ CSDs. We infer that the CSD strategies of gambling firms in Macao and the USA did not serve as vehicles for reflexivity about social responsibility or social responsiveness. Instead, the firms camouflaged legitimacy gaps about sensitive topics by adopting assertive or defensive façades, disclaiming ethical responsibility, curtailing disclosure, or offering zero disclosure. Differences between CSD strategies according to topic, location, time, and reporting channel appear to reflect four factors: pressure to report, availability of good news, whether a firm was assuming ethical responsibility for addressing the topic, and the prospective readership. This study extends our understanding of the contextual and topic-specific factors affecting the quantity and character of CSDs by firms in a contested industry.